Inclusive Education Policies and Classroom Practices for Students with Diverse Learning Needs - Farid An-Nasir; Hassan Al-Zahra (PT Mutiara Bustan Ilmu, 2026)
This study explores the implementation of inclusive education policies and classroom practices in addressing the needs of students with diverse learning abilities. Using a qualitative descriptive approach, data were collected through interviews, classroom observations, and document analysis involving teachers, school administrators, and students. The findings reveal that inclusive education practices, such as differentiated instruction, flexible assessment, and collaborative teaching, significantly enhance student participation and learning outcomes. Teachers demonstrated positive attitudes toward inclusion, although challenges such as limited resources, insufficient training, and time constraints were identified. The study also highlights the importance of institutional support, teacher collaboration, and parental involvement in strengthening inclusive practices. Overall, the results indicate that effective implementation of inclusive education requires a comprehensive approach that integrates policy, pedagogy, and continuous professional development.